HUBUNGAN KELEKATAN ORANGTUA DAN REGULASI DIRI DENGAN KEMAMPUAN SOSIAL ANAK - Pardede, Esther Novelia; Supena, Asep; Fahrurrozi, Fahrurrozi (Jurnal Pendidikan Usia Dini, 2018)
The aim of this research is to determine the relationship of parental attachment and self-regulation on social skill of 3rd grades. The research was conducted at Pangudi Luhur Elementary School Jakarta with involving of 84 samples of 3rd graders. The research method used is correlational research method. The data was collected using an assessment scale instrument. Data were analyzed by using correlation technique (regression). The results showed: (1) there was a positive correlation between parental attachment and social skill, (2) there was a positive correlation between self-regulation and social skill, (3) there was a positive correlation between parental attachment and self-regulation with social skill. The results of this study show the implication that the social skills of children can be developed by increasing parental attachment and self-regulation Keywords: parental attachment, self-regulation, social skill Tujuan dari penelitian ini adalah untuk mengetahui hubungan ketelekatan orang tua dan regulasi diri dengan kemampuan sosial anak kelas 3. Penelitian ini dilakukan di Sekolah Dasar Pangudi Luhur Jakarta dengan melibatkan 84 sampel siswa kelas 3. Metode Penelitian yang digunakan adalah metode penelitian korelasional. Pengumpulan data dilakukan dengan menggunakan instrumen skala penilaian. Data dianalisis dengan menggunakan teknik korelasi (regresi). Hasil penelitian menunjukkan : (1) terdapat hubungan yang positif antara kelekatan orangtua dengan kemampuan sosial, (2) terdapat hubungan yang positif antara regulasi diri dengan kemampuan sosial, (3) terdapat hubungan yang positif antara kelekatan orangtua dan regulasi diri dengan kemampuan sosial. Hasil penelitian ini menunjukkan implikasi bahwa, kemampuan sosial anak dapat ditingkatkan dengan cara meningkatkan kelekatan orangtua dan kemampuan regulasi diri Kata kunci: kelekatan orangtua, regulasi diri, kemampuan sosial